Assessment of health-related quality of life (HRQoL) of patients with type 2 diabetes in Turkey - GÖZÜ, HÜLYA (ELSEVIER IRELAND LTD, 2008)
We measured the health-related quality of life (HRQoL) in a sample of 376 type 2 diabetes patients in Turkey using the Diabetes Quality of Life (DQOL) instrument and examined which patient socio-demographic and diabetes-related clinical characteristics are associated with better quality of life (QoL). The influence of patient socio-demographic and clinical characteristics on QoL was examined using independent sample t-tests and one-way analysis of variance. Diabetes significantly affected the HRQoL of patients included in this study. The mean score of the total DQOL measure was higher among patients who were less than 40 years of age, male, married, had less than 8 years of education, lived with their family and had no family history of diabetes (p < 0.05). Similarly, patients with less than 5 years of disease duration, no complications or prior hospitalization, receive insulin, and with HbA(1)c < 7 reported significantly better overall HRQoL (p < 0.05). Patients with BMI < 24 had higher levels of satisfaction with diabetes than those with BMI >= 24 (p < 0.05). Diabetes-related HRQoL information is clearly of supreme importance to family physicians and policy makers to identify and implement appropriate interventions for achieving better management of diabetes and ultimately improving the QoL of diabetes patients. (c) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: type 2 diabetes; QoL; HRQoL; DQOL; 15D; GLUCOSE-INTOLERANCE; HIGH PREVALENCE; SATISFACTION; MELLITUS; OBESITY; INSULIN; TRANSPLANTATION; QUESTIONNAIRE; ADOLESCENTS; MANAGEMENT